2018
DOI: 10.1038/s41551-017-0182-x
|View full text |Cite
|
Sign up to set email alerts
|

Targeted repair of heart injury by stem cells fused with platelet nanovesicles

Abstract: Stem cell transplantation, as used clinically, suffers from low retention and engraftment of the transplanted cells. Inspired by the ability of platelets to recruit stem cells to sites of injury on blood vessels, we hypothesized that platelets might enhance the vascular delivery of cardiac stem cells (CSCs) to sites of myocardial infarction injury. Here, we show that CSCs with platelet nanovesicles fused onto their surface membranes express platelet surface markers that are associated with platelet adhesion to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
173
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 189 publications
(176 citation statements)
references
References 34 publications
0
173
0
1
Order By: Relevance
“…Due to their high specificity, antibodies and antibody fragments have been the targeting molecule of choice [75]. Recent studies also showed that platelet membranes could be utilized to target cells to the infarct heart [76]. Recent developments in phage display have yielded many new targeting molecules such as the CHP [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Due to their high specificity, antibodies and antibody fragments have been the targeting molecule of choice [75]. Recent studies also showed that platelet membranes could be utilized to target cells to the infarct heart [76]. Recent developments in phage display have yielded many new targeting molecules such as the CHP [26,27].…”
Section: Discussionmentioning
confidence: 99%
“…Several types of biomarkers have been shown to be overexpressed in diseased cardiovascular regions, which have been identified as targets for nanomedicine. Thus, ligand‐installed nanocarriers are now being investigated for their ability to target cardiovascular diseases, for instance, atherosclerosis, myocardial infarction, and heart injury ( Table 5 ).…”
Section: Targeting Strategies With Ligand‐installed Nanocarriersmentioning
confidence: 99%
“…The exact numbers of cells in myocardium was quantified by Y chromosome‐specific PCR. Quantitative PCR for the Sex‐determining Region Y gene (SRY) was performed at 1 day (after fluorescence imaging), 7 days, and 2 weeks after cell transplantation . The primers sequences for specific Y chromosome of rat were as follows: sense: 5′‐GAG CTT TGG GAG CAG TGA C‐3′, antisense: 5′‐ATG AGG CTG ATA TTT ATA GTT TGG‐3′.…”
Section: Methodsmentioning
confidence: 99%
“…Stem cell‐based regenerative therapy has not fulfilled decade's long expectations as a promising treatment for acute myocardial infarction (MI) and heart failure . The underlying reasons for the unsatisfactory results in clinical trials are complicated and not fully clarified; however, poor cell homing, retention, and engraftment are generally regarded as major obstacles to achieving a significant functional benefit .…”
Section: Introductionmentioning
confidence: 99%